The effects of a synthetic insecticide and a mineral oil on alfalfa insect pests (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2018)
The effects of the synthetic insecticide Eforia 043 ZK (thiamethoxam+lambdacyhalothrin),applied alone and at 1/5 and 2/5 reduced doses in a mix with the mineraloil Akarzin, on Tychius flavus Beck. (Coleoptera: Curculionidae), Adelphocoris lineolatusGoeze (Hemiptera: Miridae), Acyrthosiphon pisum Harr. (Hemiptera: Aphididae), harmfulthrips (Thysanoptera) and cicadas (Hemiptera: suborder Auchenorrhyncha) were studied.The efficacy of Eforia (applied alone and in reduced doses) was significantly higheragainst A. pisum, followed by A. lineolatus and harmful thrips, compared to cicadas. Theinsecticidal action of Akarzin had a better protective effect against A. pisum, followedby A. lineolatus, in comparison with thrips and cicadas. Combined application of thebroad-spectrum insecticide Eforia provided good control against insect pests. The mixof Eforia’s reduced 1/5 dose with the mineral oil showed the highest toxicity throughoutthe reporting period. Eforia applied at the reduced dose of 2/5 with Akarzin followedin efficacy. A synergistic effect was observed in combinations and was defined as subadditivesynergism. Reduced dosage of Eforia and decrease in negative environmentalimpact of the plant protection products is a friendly approach to integrated pest control.It is important to apply innovative formulations of plant protection products that are saferboth for plants and the environment.
Keywords: Synthetic insecticides; Mineral oil; Reduced doses; Efficacy; Insect pests; Alfalfa